2014
DOI: 10.1016/j.jacc.2014.01.071
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Computed Tomography Angiography for the Detection of Cardiac Allograft Vasculopathy

Abstract: CCTA using currently available technology is a reliable noninvasive imaging alternative to coronary angiography with an excellent sensitivity, specificity, and NPV for the detection of CAV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
48
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(52 citation statements)
references
References 43 publications
3
48
0
1
Order By: Relevance
“…5 Allograft vasculopathy is diffuse, involving large epicardial and smaller intramyocardial arteries, and its course is unpredictable, and often clinically silent due to denervation. 6 Approximately 10% of patients die in the 12 months following a diagnosis of cardiac allograft vasculopathy. 1 Yet, there are available therapies such as pharmacologic inhibition/modulation of cellular proliferative signaling, which have been associated with reduced incidence and slower progression 6 ; thus the need for early and accurate detection is paramount.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…5 Allograft vasculopathy is diffuse, involving large epicardial and smaller intramyocardial arteries, and its course is unpredictable, and often clinically silent due to denervation. 6 Approximately 10% of patients die in the 12 months following a diagnosis of cardiac allograft vasculopathy. 1 Yet, there are available therapies such as pharmacologic inhibition/modulation of cellular proliferative signaling, which have been associated with reduced incidence and slower progression 6 ; thus the need for early and accurate detection is paramount.…”
mentioning
confidence: 99%
“…6 Approximately 10% of patients die in the 12 months following a diagnosis of cardiac allograft vasculopathy. 1 Yet, there are available therapies such as pharmacologic inhibition/modulation of cellular proliferative signaling, which have been associated with reduced incidence and slower progression 6 ; thus the need for early and accurate detection is paramount. Invasive catheter-based conventional coronary angiography has long been the See related article, pp.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…45 CCTA has a sensitivity of up to 89% and an excellent negative predictive value of 97% for CAV. 46 In a recent meta-analysis, the newest-generation CCTA ($$16 slices) was compared to coronary angiography and IVUS and the analysis showed that CCTA was accurate in excluding CAV in the majority of OHT patients, especially when compared to standard coronary angiography. When compared to IVUS, the sensitivity and negative predictive value of CCTA was lower (81% and 50%, respectively), likely because CT is designed to assess the lumen size and not intimal hyperplasia.…”
mentioning
confidence: 99%